Self Condensation Reaction of Thiosalicylic Acid in the Presence of Some Transition Metal Ions - S.M. Nasman, Omar; M. Baraka, Rajai; M. Abdul Aziz, Hassan (Asian Journal of Chemistry, 2010)
A new series of 16-membered tetrathiamacrocyclic complexes have been synthesized by the selfcondensation of thiosalicylic acid in the presence of transition metal ions and have been characterized by elemental analyses, IR, 1H NMR, electronic spectral data, conductivity, and magnetic susceptibility measurements. An octahedral geometry around the metal ion has been suggested for the nickel, cobalt and zinc complexes, while a square-planar geometry is proposed for the copper complexes.